It's difficult to change the way we teach: lessons from the Integrative Themes in Physiology curriculum module project - Silverthorn, Dee U; Thorn, Patti M; Svinicki, Marilla D (Advances in physiology education, 2006)
1 Department of Integrative Biology, University of Texas, Austin, Texas 2 Science Education Center, Department of Curriculum and Instruction, University of Texas, Austin, Texas 3 Center for Teaching Effectiveness, University of Texas, Austin, Texas Address for reprint requests and other correspondence: D. U. Silverthorn, Dept. of Integrative Biology, Univ. of Texas, 1 Univ. Station, C0930, Austin, TX 78712 (e-mail: silverthornatmail.utexas.edu ) The Integrative Themes in Physiology (ITIP) project was a National Science Foundation-funded collaboration between the American Physiological Society (APS) and the Human Anatomy and Physiology Society (HAPS). The project goal was to create instructional resources that emphasized active learning in undergraduate anatomy and physiology classrooms. The resources (activity modules and professional development) addressed two factors thought to be limiting science education reform: instructors' knowledge of how to implement active learning instruction and time to design innovative curricula. Volunteer instructors with a strong interest in using active learning in their classrooms were recruited to use the ITIP modules and provide ease-of-use feedback and student assessment data. As the study unfolded, instructor attrition was higher than had been anticipated, with 17 of 36 instructors withdrawing. More surprisingly, instructors remaining with the project failed to use the modules and reported specific obstacles that precluded module use, including lack of support from academic leadership, unplanned class size increases and heavy teaching loads, a union strike, insufficient time to develop a mindset for change, inadequate technology/funding, an adverse human subjects ruling, incompatibility of modules with instructors' established content and expectations, and personal factors. Despite the lack of module use and obstacles, 8 of 19 site testers began independently to introduce new active learning instruction into their classrooms. In the larger picture, however, it is important to note that only 8 of the initial 36 volunteers (22%) actually ended up changing their instruction to include opportunities for student active learning. These findings underscore the difficulty of implementing instructional change in college classrooms. Key words: active learning; curriculum development; faculty development; science education reform; instructional change obstacles